How is the mental toughness of student-athletes? An investigation of elite student-athletes in Bengkulu City - Dian Pujianto; Yahya Eko Nopiyanto; Ipa Sari Kardi (Journal Sport Area, 2022)
The objectives to be achieved in this study are knowing the level of the mental toughness of student-athletes in Bengkulu City. This research applies a quantitative descriptive method through a causal-comparative design. The research population was 34 student-athletes from 5 sports. Determination of the sample using purposive random sampling. Data were collected using the Mental Toughness in Sport Questionnaire instrument. The data analysis technique uses standard deviation and the ideal mean to determine the level of the mental toughness of student-athletes, meanwhile to determine the level of the mental toughness of student-athletes who are reviewed based on sport and gender by hypothesis testing (one-way ANOVA and t-test) using SPSS. The results of data analysis found the category of the mental toughness of student-athletes in Bengkulu City was very high and there were no differences in the mental toughness of athletes from each sport and gender. However, this study has not yet discussed the strategies and mental training programs implemented by athletes in each sport. Therefore, it is recommended that researchers who have an interest in continuing this research are advised to study further the strategies and programs of athletes' mental training.